Engineering Education in Iberian America - Ciampi, Melany M. (2011)
The large Continent of America has in its territory besides overseas regions, dependencies and colonies 35 sovereign countries, 25 in North America and 12 in South America. Among them there are two big countries Brazil, which official language is Portuguese and Argentina, which official language is Spanish. Both are of political and economical importance in South America. They both belong to the so called Iberian America, which is a term used since the second half of the 19th century to refer collectively to the countries in the Americas, which were formerly colonies of Spain or Portugal. The Iberian countries in Europe are Portugal, Spain, Andorra and Gibraltar. The objective of this paper is to present the history and he current status of engineering education in Iberian America countries Brazil and Argentina followed by the countries that originated the engineering education in these countries, Portugal and Spain.